2023
DOI: 10.2196/50357
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Health Care Professionals Using Digital Tools in the Hospital: Qualitative Systematic Review

Marie Wosny,
Livia Maria Strasser,
Janna Hastings

Abstract: Background The digitalization of health care has many potential benefits, but it may also negatively impact health care professionals’ well-being. Burnout can, in part, result from inefficient work processes related to the suboptimal implementation and use of health information technologies. Although strategies to reduce stress and mitigate clinician burnout typically involve individual-based interventions, emerging evidence suggests that improving the experience of using health information technol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
(514 reference statements)
0
8
0
Order By: Relevance
“…Overall, negative sentiments about the use of digital tools have been mentioned more often by HCPs (n=3018, 50.62% quotations) compared with positive (n=1636, 27.44% quotations) or neutral (n=1308, 21.94% quotations) reports. Compared with our previous literature review and derived theoretical framework [ 31 ], which included 6 dimensions impacting digital tool use, including moderators, outcomes, and experiences, each of a positive and negative nature, this study reported a similar distribution of digital tool moderators, outcomes, and experiences (n=2976). Investigating these 6 dimensions, overall, 61.32% (1825/2976) of reported factors are moderators that influence the use of digital tools in positive (883/2976, 29.67%) or negative (942/2976, 31.65%) ways; 31.65% (942/2976) are outcomes, either positive (438/2976, 14.72%) or negative (504/2976, 16.93%); and only 7.02% (209/2976) true experiences and emotions, with only 1.88% (56/2976) positive and 5.14% (153/2976) negative reports that impact the overall well-being of clinicians.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Overall, negative sentiments about the use of digital tools have been mentioned more often by HCPs (n=3018, 50.62% quotations) compared with positive (n=1636, 27.44% quotations) or neutral (n=1308, 21.94% quotations) reports. Compared with our previous literature review and derived theoretical framework [ 31 ], which included 6 dimensions impacting digital tool use, including moderators, outcomes, and experiences, each of a positive and negative nature, this study reported a similar distribution of digital tool moderators, outcomes, and experiences (n=2976). Investigating these 6 dimensions, overall, 61.32% (1825/2976) of reported factors are moderators that influence the use of digital tools in positive (883/2976, 29.67%) or negative (942/2976, 31.65%) ways; 31.65% (942/2976) are outcomes, either positive (438/2976, 14.72%) or negative (504/2976, 16.93%); and only 7.02% (209/2976) true experiences and emotions, with only 1.88% (56/2976) positive and 5.14% (153/2976) negative reports that impact the overall well-being of clinicians.…”
Section: Resultsmentioning
confidence: 68%
“…Unlike other research methods, qualitative interviews allow us to capture intricate aspects of individuals’ experiences, including their thoughts, emotions, opinions, and perspectives [ 36 - 38 ]. Switzerland was chosen as the study location partly due to the limited exploration of its diverse health care digitalization landscape [ 31 ]. Moreover, Switzerland’s health care system is decentralized; therefore, there are a variety of solutions implemented at different hospitals, offering a rich source of diverse experiences.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations